Rate-of-Return Regulation and Utility Capital Structure Decision - Taggart, Robert A. (Journal of Finance, 1981)
Robert A. Taggart, Jr., Rate-of-Return Regulation and Utility Capital Structure Decision, The Journal of Finance, Vol. 36, No. 2, Papers and Proceedings of the Thirty Ninth Annual Meeting American Finance Association, Denver, September 5-7, 1980 (May, 1981), pp. 383-393